2017
DOI: 10.1080/09540121.2017.1307922
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health worker stigma and uptake of HIV counseling and testing and utilization of non-HIV health services: the experience of male and female sex workers in Kenya

Abstract: The barrier HIV-stigma presents to the HIV treatment cascade is increasingly documented; however less is known about female and male sex worker engagement in and the influence of sex-work stigma on the HIV care continuum. While stigma occurs in all spheres of life, stigma within health services may be particularly detrimental to health seeking behaviors. Therefore, we present levels of sex-work stigma from healthcare workers (HCW) among male and female sex workers in Kenya, and explore the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
3
52
1
Order By: Relevance
“…84 Although the majority of women had sought ANC at last pregnancy, it is has been documented that FSWs as well as young, unmarried women commonly face stigma in ANC services and subsequently may avoid disclosure, thus limiting access to appropriate services. [85][86][87] In our case, we identified associations between health care-related stigma and current use of nonbarrier contraception. Strengthening bidirectional collaborations between FSW-oriented services and ANC may foster more equitable access to quality and respectful family planning and ANC services for FSWs, including women living with HIV.…”
Section: Discussionmentioning
confidence: 79%
“…84 Although the majority of women had sought ANC at last pregnancy, it is has been documented that FSWs as well as young, unmarried women commonly face stigma in ANC services and subsequently may avoid disclosure, thus limiting access to appropriate services. [85][86][87] In our case, we identified associations between health care-related stigma and current use of nonbarrier contraception. Strengthening bidirectional collaborations between FSW-oriented services and ANC may foster more equitable access to quality and respectful family planning and ANC services for FSWs, including women living with HIV.…”
Section: Discussionmentioning
confidence: 79%
“… Context: Stigma and discrimination remain important barriers to HIV testing , and about half of all people living with HIV do not know their status . Accordingly, closing the testing gap via differentiated service models, tailored approaches for populations at risk, and stigma reduction strategies is central to Treat All implementation .…”
Section: Resultsmentioning
confidence: 99%
“…Other research has indicated that men utilize mental health services less frequently than women due to masculine gender socialization [38]. Furthermore, the fear of discrimination may also explain low mental health service usage [39][40][41].…”
Section: Discussionmentioning
confidence: 99%